PENCAPAIAN KEMAMPUAN BERPIKIR KRITIS MELALUI PEMBELAJARAN OPEN ENDED PADA MATERI BANGUN DATAR - yani komalasari; resty tasya; Neni maryani; Fitriani nursalamah; nani marlina; wahyu hidayat (IKIP Siliwangi, 2019)
The purpose of this research is to describe the achievement of critical thinking ability of mathematics students in the junior high school using open ended learning. Population of this research is all of students 1st grade inn SMP Negeri 3 Soreang consists of 10 classes. From those population was taken two classes, first VII I class with 28 students used an open ended approach learning and VII J with 29 students used a conventional learning. The instrument is used to collecting data are test question critical thinking test with five indicator(1) Check the truth of arguments, acknowledgment and processes of solution (2) Drawing the question with the reason (3) Identifying relevant and irrelevant data on a mathematics problem (4) identifying assumptions (5) Answer/finish the problem mathematics with the reason. To the test achievement of the learning with used open ended approach learning and conventional learning used normality test. To compare the of open ended learning and conventional learning, analyzed used two achievement sample t-test. The result of this research shows that a whole spectrum of critical thinking abilities there is a difference between using open ended approach learning and conventional learning.